A PSYCHOLINGUISTIC ANALYSIS OF THE ENGLISH STUDENT’ LANGUAGE DISORDER ON LANGUAGE COMPREHENSION IN LITERATURE COURSE - Siti Ithriyah (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
This research just focuses on analyzing comprehension disorder from language disorder, psycholinguistics is the discipline that investigates and describes the psychological processes that make it possible for humans to master and use language. The expert conduct research on speech development and language development and how individuals of all ages comprehend and produce language. Students with this issue may also struggle with basic reading skills such as decoding words, but comprehension is the greater weakness. Some students with a learning disability in reading comprehension can read aloud with little or no difficulty pronouncing words, but they do not understand or remember what they've read. This research uses descriptive qualitative with describes language disorder and attempts to explore the application of sentence from as language disorder on language comprehension utterances which are spoken by English student’ Literature in ELT course. Researchers will collect the data from tasks’ students in the class and look for how they analyzed the task such as: short story, Prose, Poetry, movie, and drama. The data are analyzed by classifying and analyzing the data into kinds of comprehension disorder from language disorder and contexts by using Ginsberg theory. The research will be found that students during studying literature in ELT have troubles in his language, especially in the language comprehension. Problems that may be experienced can involve grammar (syntax and/or morphology), semantics (meaning), or other aspects of language.